Music mnemonics aid Verbal Memory and Induce Learning – Related Brain Plasticity in Multiple Sclerosis - Thaut, Michael H.; Peterson, David A.; McIntosh, Gerald C.; Hoemberg, Volker (Frontiers in Human Neuroscience, 2014)
Recent research in music and brain function has suggested that the temporal pattern structure in music and rhythm can enhance cognitive functions. To further elucidate this question specifically for memory we investigated if a musical template can enhance verbal learning in patients with multiple sclerosis and if music assisted learning will also influence short-term, system-level brain plasticity. We measured systems-level brain activity with oscillatory network synchronization during music assisted learning. Specifically, we measured the spectral power of 128-channel electroencephalogram (EEG) in alpha and beta frequency bands in 54 patients with multiple sclerosis (MS). The study sample was randomly divided into 2 groups, either hearing a spoken or musical (sung) presentation of Rey’s Auditory Verbal Learning Test (RAVLT). We defined the “learning-related synchronization” (LRS) as the percent change in EEG spectral power from the first time the word was presented to the average of the subsequent word encoding trials. LRS differed significantly between the music and spoken conditions in low alpha and upper beta bands. Patients in the music condition showed overall better word memory and better word order memory and stronger bilateral frontal alpha LRS than patients in the spoken condition. The evidence suggests that a musical mnemonic recruits stronger oscillatory network synchronization in prefrontal areas in MS patients during word learning. It is suggested that the temporal structure implicit in musical stimuli enhances ‘deep encoding’ during verbal learning and sharpens the timing of neural dynamics in brain networks degraded by demyelination in MS